The Role Of The Ideas Of Malomatism In The Development Of Islamic Mysticism Tasawwuf - Yazdonov Zikirillo Shukurilloevich (Zien Journals, 2024)
This article philosophically analyzes the role of the malomatism (reproof) ideas which arose on the basis of the tariqa of tasawwuf (Sufism), in the development of Islamic Sufism. The cultural development of various tariqas and teachings in interconnection is scientifically substantiated.
Keywords: Malomat; nafs; hypocrisy